Shale core wettability alteration, foam and emulsion stabilization by surfactant: Impact of surfactant concentration, rock surface roughness and nanoparticles - Okunade, O.A. (Elsevier B.V., 2021)
Hexadecyltrimethyl ammonium bromide (HCTAB) and sodium dodecyl sulfate (SDS) are popular conventional surfactants with versatile industrial and oilfield applications. Knowledge of the optimum conditions for their applications for shale rock wettability modification, as well as foam and emulsion stabilization is relevant for hydrocarbon recovery process optimization. Influence of surfactant concentration, rock surface roughness and presence of nanoparticles in surfactant solutions on contact angles, oil-water interfacial tension (IFT), as well as foam and emulsion stabilization by HCTAB and SDS was investigated in this study. The interfacial properties measurements were conducted with Drop Shape Analyser (DSA 25), whereas the foam generation and stability properties were investigated via dynamic foam analyzer (DFA100). The emulsion stabilization and demulsification processes were investigated in Formulaction Turbiscan. Results showed an existence of optimum concentration of surfactant for obtaining the lowest contact angles, oil-water IFT reduction, as well as attaining maximum foam stability. The contact angle measured on rough core surfaces were smaller than the contact angle measured on smooth surfaces. Contact angles increased with increasing salnity concentration, but decreased with the increasing rock saturation time. Oil was more detrimental to foam stability when the generated foam was brought into contact with the resident oil, compared to when oil was added to the foaming solutions before foam generation. Lower contact angles, durable foam, and stable emulsion were produced in presence of oil and at high temperature via the synergy of nanoparticles and surfactants. Almost 66 decreased in contact angle was achieved with carbon nanotubes-SDS solutions, whereas Al2O3 nanoparticles-HCTAB foam attained a viscosity of 99 mPa-s at 60 Â°C. The foam demonstrated shear thinning Newtonian fluids behaviors but attained a plateau after sometimes. The study suggests the conditions for optimization of conventional surfactants applications in conventional and unconventional reservoir. Â© 2021 Elsevier B.V.